Helminth communities in eels Anguilla anguilla from Adriatic coastal lagoons in Italy - DI CAVE, DAVID; BERRILLI, FEDERICA; De Liberato, C; ORECCHIA, PAOLA; Kennedy, C. (Cambridge University Press, 2001)
The composition and diversity of the total and intestinal component and infra-communities were determined in eels Anguilla anguilla from three shallow lagoons on the Adriatic coast of Italy to determine whether the helminth communities would differ in composition and structure from those in eels from lagoons on the Tyrrhenian coast. The lagoons differed in respect of their management regimes and the extent of freshwater influx. Both freshwater and marine species of helminths were found in the eels in all three lagoons, but the freshwater component was richer in Valle Figheri. A suite of three digenean eel specialist species occurred in all three lagoons, of which any two members dominated each community. This conferred a high degree of similarity between the communities of the three lagoons. The same three species also dominated helminth communities in eels in lagoons along the Tyrrhenian coast of Italy, and compositional similarity levels were similar within and between western and eastern groups. Species richness was higher in the component communities of the eels of the Adriatic lagoons when compared to the Tyrrhenian ones, but diversity and dominance indices were of a similar order of magnitude and range. Intestinal helminth communities were richer and more diverse in two of the Adriatic lagoons because the proportion of eels with zero or one helminth species was, unusually, in the minority. It was nevertheless concluded that infracommunity structure was similar in eels from both western and eastern lagoons and that the hypothesis that it would differ in Adriatic lagoons could not be supported. The findings provide further evidence of the similarity in composition and structure of helminth communities in eels from coastal lagoons throughout Europe.